2018
DOI: 10.1097/md.0000000000009610
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and urodynamic characteristics of underactive bladder

Abstract: There have no universally accepted criteria and have been established for classification of underactive bladder (UAB) at present. Thus, the study described the comprehensive clinical and urodynamic characteristics of UAB in patients with lower urinary tract symptoms.A total of 1726 patients (1259 men and 467 women; 6–88 years old) who were admitted to our center with a diagnosis of UAB were included in this retrospective study. It was due to the type of rehabilitation hospital, so higher percentage of neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
(20 reference statements)
0
26
0
Order By: Relevance
“…The urodynamic findings of UAB include DU, an acontractile detrusor, and detrusor hyperactivity with impaired contractility (DHIC). Although DHIC is associated with urgency urinary incontinence (UUI), it does not account for much of the UAB population [7]. SUI, a type of urethral sphincter dysfunction, is more likely to be associated with UAB involving incontinence.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The urodynamic findings of UAB include DU, an acontractile detrusor, and detrusor hyperactivity with impaired contractility (DHIC). Although DHIC is associated with urgency urinary incontinence (UUI), it does not account for much of the UAB population [7]. SUI, a type of urethral sphincter dysfunction, is more likely to be associated with UAB involving incontinence.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The voiding difficulty might be aggravated by using antimuscarinics for the treatment of DO, resulting in chronic or acute urinary retention in patients with DU and DO respectively. 22 Medical treatment has been given to the majority of the patients, which might be reflected with missed diagnosis due to the long duration of the prevalent problem and overlap of DU characteristics with other common symptoms such as bladder overactivity, urinary tract infections, and BOO. 23 , 24 The findings of the current study are supported by the findings of Rademakers et al, 25 who reported a prevalent increase of hesitancy, weak stream, and incomplete bladder emptying in women with DU as compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Since cavernous nerve injury during pelvic surgery results in erectile dysfunction in 50% of male patients, this is an active area of neuroregeneration research [35]. While not currently being investigated, these approaches could also be used to prevent underactive bladder symptoms, which can be caused by SCI, pelvic fractures, or nerve injury during pelvic surgery [36]. Any therapy that could increase regeneration associated genes would also help neuroregeneration after injuries or trauma when normal upregulation is either blunted or non-existent, such as occurs in childbirth which results in impaired regeneration of the pudendal nerve and reinnervation of the external urethral sphincter [37,38].…”
Section: Nerve Regenerationmentioning
confidence: 99%